Solve (1-x^2) y''+2xy'-2y=0, y1=x (one of the solutions)
We introduce an additional variable z such that y=xz. Then
"y' = z + xz'"
"y'' = 2z' + xz''"
"(1-x^2)y'' + 2xy' -2y = (1-x^2)(2z' + xz'') +2x (z+xz') - 2xz = x(1-x^2)z'' + 2z'=0" "\\frac{z''}{z'} = \\frac{2}{x(x^2-1)} = \\frac{1}{x-1} + \\frac{1}{x+1} - \\frac{2}{x} = \\frac{d}{dx}\\ln |\\frac{x^2-1}{x^2}| = \\frac{d}{dx}\\ln |z'|"
from where we have
"|z'| = c|1-x^{-2}|"
if z' is differentiable everywhere besides 0, then "z' = c(1-x^{-2})"
"z = c(x+x^{-1})+c'"
"y=xz=c(x^2+1)+c'x"
Comments
Leave a comment